Ventricular Zone Disruption in Human Neonates With Intraventricular Hemorrhage. Issue 5 (16th May 2017) - McAllister, James P.; Guerra, Maria Montserrat; Ruiz, Leandro Castaneyra; Jimenez, Antonio J.; Dominguez-Pinos, Dolores; Sival, Deborah; den Dunnen, Wilfred; Morales, Diego M.; Schmidt, Robert E.; Rodriguez, Esteban M.; Limbrick, David D.
Abstract : To determine if ventricular zone (VZ) and subventricular zone (SVZ) alterations are associated with intraventricular hemorrhage (IVH) and posthemorrhagic hydrocephalus, we compared postmortem frontal and subcortical brain samples from 12 infants with IVH and 3 nonneurological disease controls without hemorrhages or ventriculomegaly. Birth and expiration estimated gestational ages were 23.0–39.1 and 23.7–44.1 weeks, respectively; survival ranges were 0–42 days (median, 2.0 days). Routine histology and immunohistochemistry for neural stem cells (NSCs), neural progenitors (NPs), multiciliated ependymal cells (ECs), astrocytes (AS), and cell adhesion molecules were performed. Controls exhibited monociliated NSCs and multiciliated ECs lining the ventricles, abundant NPs in the SVZ, and medial vs. lateral wall differences with a complex mosaic organization in the latter. In IVH cases, normal VZ/SVZ areas were mixed with foci of NSC and EC loss, eruption of cells into the ventricle, cytoplasmic transposition of N-cadherin, subependymal rosettes, and periventricular heterotopia. Mature AS populated areas believed to be sites of VZ disruption. The cytopathology and extension of the VZ disruption correlated with developmental age but not with brain hemorrhage grade or location. These results corroborate similar findings in congenital hydrocephalus in animals and humans and indicate that VZ disruption occurs consistently in premature neonates with IVH.